Low-complexity despreading scheme with repetition code for wireless body area networks - Yu CHI; Lan CHEN; Chao LV (Tongxin xuebao)
To improve the reliability of data transmission and reduce the complexity of the narrow band receiver for wireless body area networks(WBAN),spreading with repetition code is used in IEEE 802.15.6 standard.A despreading structure in which the metrics of reliability were calculated selectively according to the dynamic threshold was designed.Combined with hard decision,hard threshold-combine and hard threshold-delete despreading methods by simplifying maximal ratio combining and generalized minimum distance principle respectively were proposed,which had low complexity and near-optimal performance.The theoretical analysis and simulation results show that compared to despreading based on maximum likelihood method,the spreading gain of the proposed methods is close to the theoretical value and the computational complexity can be reduced by 86% at most under high SNR circumstances.